An acoustic beam shifter with enhanced transmission using perforated metamaterials. (15th January 2015) - Wei, Pengjiang; Liu, Fu; Liang, Zixian; Xu, Yan; Chu, Sai Tak; Li, Jensen
Abstract: We experimentally demonstrate an acoustic beam shifter with enhanced transmission based on subwavelength perforated metamaterials with a wide working frequency range from 2.8 to 4.6 kHz. An oblique perforation angle allows a flexible beam shifting distance and negative refraction for one side of incidence angles. While the beam shifting action is broadband due to the geometric nature of design, beam shifting with enhanced efficiency is found at the frequency with Fabry-Pérot (FP) resonance through a two-dimensional pressure field mapping. Such a method in combining extraordinary transmission and beam shifting with properly designed metamaterials, enables designing flexible and also transformation acoustic devices with high transmission efficiency in a general context.